On improving chemical engineering education in the Philippines. - Jose, Wilfredo I.
The task of improving chemical engineering education admits of two solutions. We can first consider the needs of the non-academic sector and then we can look at the problems from the viewpoint of the academe itself. Various specific programs of action are proposed based on the experience of the University of the Philippines Department of Chemical Engineering.